The iterative optimal brain surgeon: Faster sparse recovery by leveraging second-order information - Wu, Diyuan; Modoranu, Ionut-Vlad; Safaryan, Mher; Kuznedelev, Denis; Alistarh, Dan-Adrian (38th Conference on Neural Information Processing Systems)
The rising footprint of machine learning has led to a focus on imposing model sparsity as a means of reducing computational and memory costs. For deep neural networks (DNNs), the state-of-the-art accuracy-vs-sparsity is achieved by heuristics inspired by the classical Optimal Brain Surgeon (OBS) framework [LeCun et al., 1989, Hassibi and Stork, 1992, Hassibi et al., 1993], which leverages loss curvature information to make better pruning decisions. Yet, these results still lack a solid theoretical understanding, and it is unclear whether they can be improved by leveraging connections to the wealth of work on sparse recovery algorithms. In this paper, we draw new connections between these two areas and present new sparse recovery algorithms inspired by the OBS framework that comes with theoretical guarantees under reasonable assumptions and have strong practical performance. Specifically, our work starts from the observation that we can leverage curvature information in OBS-like fashion upon the projection step of classic iterative sparse recovery algorithms such as IHT. We show for the first time that this leads both to improved convergence bounds under standard assumptions. Furthermore, we present extensions of this approach to the practical task of obtaining accurate sparse DNNs, and validate it experimentally at scale for Transformer-based models on vision and language tasks.

PV-tuning: Beyond straight-through estimation for extreme LLM compression - Malinovskii, Vladimir; Mazur, Denis; Ilin, Ivan; Kuznedelev, Denis; Burlachenko, Konstantin; Yi, Kai; Alistarh, Dan-Adrian; Richtarik, Peter (38th Conference on Neural Information Processing Systems)
There has been significant interest in "extreme" compression of large language models (LLMs), i.e. to 1-2 bits per parameter, which allows such models to be executed efficiently on resource-constrained devices. Existing work focused on improved one-shot quantization techniques and weight representations; yet, purely post-training approaches are reaching diminishing returns in terms of the accuracy-vs-bit-width trade-off. State-of-the-art quantization methods such as QuIP# and AQLM include fine-tuning (part of) the compressed parameters over a limited amount of calibration data; however, such fine-tuning techniques over compressed weights often make exclusive use of straight-through estimators (STE), whose performance is not well-understood in this setting. In this work, we question the use of STE for extreme LLM compression, showing that it can be sub-optimal, and perform a systematic study of quantization-aware fine-tuning strategies for LLMs.We propose PV-Tuning - a representation-agnostic framework that generalizes and improves upon existing fine-tuning strategies, and provides convergence guarantees in restricted cases.On the practical side, when used for 1-2 bit vector quantization, PV-Tuning outperforms prior techniques for highly-performant models such as Llama and Mistral. Using PV-Tuning, we achieve the first Pareto-optimal quantization for Llama-2 family models at 2 bits per parameter.

Spinal neuron diversity scales exponentially with swim-to-limb transformation during frog metamorphosis - Vijatovic, David; Toma, Florina Alexandra; Harrington, Zoe P; Sommer, Christoph M; Hauschild, Robert; Trevisan, Alexandra J.; Chapman, Phillip; Julseth, Mara; Brenner-Morton, Susan; Gabitto, Mariano I.; Dasen, Jeremy S.; Bikoff, Jay B.; et al. (bioRxiv)
Vertebrates exhibit a wide range of motor behaviors, ranging from swimming to complex limb-based movements. Here we take advantage of frog metamorphosis, which captures a swim-to-limb-based movement transformation during the development of a single organism, to explore changes in the underlying spinal circuits. We find that the tadpole spinal cord contains small and largely homogeneous populations of motor neurons (MNs) and V1 interneurons (V1s) at early escape swimming stages. These neuronal populations only modestly increase in number and subtype heterogeneity with the emergence of free swimming. In contrast, during frog metamorphosis and the emergence of limb movement, there is a dramatic expansion of MN and V1 interneuron number and transcriptional heterogeneity, culminating in cohorts of neurons that exhibit striking molecular similarity to mammalian motor circuits. CRISPR/Cas9-mediated gene disruption of the limb MN and V1 determinants FoxP1 and Engrailed-1, respectively, results in severe but selective deficits in tail and limb function. Our work thus demonstrates that neural diversity scales exponentially with increasing behavioral complexity and illustrates striking evolutionary conservation in the molecular organization and function of motor circuits across species.

Eigenstate thermalisation at the edge for Wigner matrices - Cipolloni, Giorgio; Erdös, László; Henheik, Sven Joscha (arXiv)
We prove the Eigenstate Thermalisation Hypothesis for Wigner matrices uniformly in the entire spectrum, in particular near the spectral edges, with a bound on the fluctuation that is optimal for any observable. This complements earlier works of Cipolloni et. al. (Comm. Math. Phys. 388, 2021; Forum Math., Sigma 10, 2022) and Benigni et. al. (Comm. Math. Phys. 391, 2022; arXiv: 2303.11142) that were restricted either to the bulk of the spectrum or to special observables. As a main ingredient, we prove a new multi-resolvent local law that optimally accounts for the edge scaling.

Cusp universality for correlated random matrices - Erdös, László; Henheik, Sven Joscha; Riabov, Volodymyr (arXiv)
For correlated real symmetric or complex Hermitian random matrices, we prove that the local eigenvalue statistics at any cusp singularity are universal. Since the density of states typically exhibits only square root edge or cubic root cusp singularities, our result completes the proof of the Wigner-Dyson-Mehta universality conjecture in all spectral regimes for a very general class of random matrices. Previously only the bulk and the edge universality were established in this generality [arXiv:1804.07744], while cusp universality was proven only for Wigner-type matrices with independent entries [arXiv:1809.03971, arXiv:1811.04055]. As our main technical input, we prove an optimal local law at the cusp using the Zigzag strategy, a recursive tandem of the characteristic flow method and a Green function comparison argument. Moreover, our proof of the optimal local law holds uniformly in the spectrum, thus also re-establishing universality of the local eigenvalue statistics in the previously studied bulk [arXiv:1705.10661] and edge [arXiv:1804.07744] regimes.

Multi-band superconductors have enhanced critical temperatures - Henheik, Sven Joscha; Langmann, Edwin; Lauritsen, Asbjørn Bækgaard (arXiv)
We introduce a multi-band BCS free energy functional and prove that for a multi-band superconductor the effect of inter-band coupling can only increase the critical temperature, irrespective of its attractive or repulsive nature and its strength. Further, for weak coupling and weaker inter-band coupling, we prove that the dependence of the increase in critical temperature on the inter-band coupling is (1) linear, if there are two or more equally strongly superconducting bands, or (2) quadratic, if there is only one dominating band.

Response theory for locally gapped systems - Henheik, Sven Joscha; Wessel, Tom (arXiv)
We introduce a notion of a local gap for interacting many-body quantum lattice systems and prove the validity of response theory and Kubo's formula for localized perturbations in such settings. On a high level, our result shows that the usual spectral gap condition, concerning the system as a whole, is not a necessary condition for understanding local properties of the system. More precisely, we say that an equilibrium state ρ0 of a Hamiltonian H0 is locally gapped in Λgap⊂Λ, whenever the Liouvillian −i[H0,⋅] is almost invertible on local observables supported in Λgap when tested in ρ0. To put this into context, we provide other alternative notions of a local gap and discuss their relations. The validity of response theory is based on the construction of non-equilibrium almost stationary states (NEASSs). By controlling locality properties of the NEASS construction, we show that response theory holds to any order, whenever the perturbation \(ε V\) acts in a region which is further than |logϵ| away from the non-gapped region Λ∖Λgap.

Experimental evaluation of fully dynamic k-means via coresets - Henzinger, Monika H; Saulpic, David; Sidl, Leonhard (2024 Proceedings of the Symposium on Algorithm Engineering and Experiments)
For a set of points in Rd, the Euclidean k-means problems consists of finding k centers such that the sum of distances squared from each data point to its closest center is minimized. Coresets are one the main tools developed recently to solve this problem in a big data context. They allow to compress the initial dataset while preserving its structure: running any algorithm on the coreset provides a guarantee almost equivalent to running it on the full data. In this work, we study coresets in a fully-dynamic setting: points are added and deleted with the goal to efficiently maintain a coreset with which a k-means solution can be computed. Based on an algorithm from Henzinger and Kale [ESA'20], we present an efficient and practical implementation of a fully dynamic coreset algorithm, that improves the running time by up to a factor of 20 compared to our non-optimized implementation of the algorithm by Henzinger and Kale, without sacrificing more than 7% on the quality of the k-means solution.

Parity-conserving Cooper-pair transport and ideal superconducting diode in planar germanium - Valentini, Marco; Sagi, Oliver; Baghumyan, Levon; de Gijsel, Thijs; Jung, Jason; Calcaterra, Stefano; Ballabio, Andrea; Aguilera Servin, Juan L; Aggarwal, Kushagra; Janik, Marian; Adletzberger, Thomas; Seoane Souto, Rubén; et al. (Nature Communications)
Superconductor/semiconductor hybrid devices have attracted increasing interest in the past years. Superconducting electronics aims to complement semiconductor technology, while hybrid architectures are at the forefront of new ideas such as topological superconductivity and protected qubits. In this work, we engineer the induced superconductivity in two-dimensional germanium hole gas by varying the distance between the quantum well and the aluminum. We demonstrate a hard superconducting gap and realize an electrically and flux tunable superconducting diode using a superconducting quantum interference device (SQUID). This allows to tune the current phase relation (CPR), to a regime where single Cooper pair tunneling is suppressed, creating a sin(2y) CPR. Shapiro experiments complement this interpretation and the microwave drive allows to create a diode with ≈ 100% efficiency. The reported results open up the path towards integration of spin qubit devices, microwave resonators and (protected) superconducting qubits on the same silicon technology compatible platform.

Time-lapse imaging of cortical projection neuron migration in mice using mosaic analysis with double markers - Hansen, Andi H; Hippenmeyer, Simon (STAR Protocols)
Mosaic analysis with double markers (MADM) technology enables the sparse labeling of genetically defined neurons. We present a protocol for time-lapse imaging of cortical projection neuron migration in mice using MADM. We describe steps for the isolation, culturing, and 4D imaging of neuronal dynamics in MADM-labeled brain tissue. While this protocol is compatible with other single-cell labeling methods, the MADM approach provides a genetic platform for the functional assessment of cell-autonomous candidate gene function and the relative contribution of non-cell-autonomous effects. For complete details on the use and execution of this protocol, please refer to Hansen et al. (2022),1 Contreras et al. (2021),2 and Amberg and Hippenmeyer (2021).3

Adhesion-induced cortical flows pattern E-cadherin-mediated cell contacts - Arslan, Feyza N; Hannezo, Edouard B; Merrin, Jack; Loose, Martin; Heisenberg, Carl-Philipp J (Current Biology)
Metazoan development relies on the formation and remodeling of cell-cell contacts. Dynamic reorganization of adhesion receptors and the actomyosin cell cortex in space and time plays a central role in cell-cell contact formation and maturation. Nevertheless, how this process is mechanistically achieved when new contacts are formed remains unclear. Here, by building a biomimetic assay composed of progenitor cells adhering to supported lipid bilayers functionalized with E-cadherin ectodomains, we show that cortical F-actin flows, driven by the depletion of myosin-2 at the cell contact center, mediate the dynamic reorganization of adhesion receptors and cell cortex at the contact. E-cadherin-dependent downregulation of the small GTPase RhoA at the forming contact leads to both a depletion of myosin-2 and a decrease of F-actin at the contact center. At the contact rim, in contrast, myosin-2 becomes enriched by the retraction of bleb-like protrusions, resulting in a cortical tension gradient from the contact rim to its center. This tension gradient, in turn, triggers centrifugal F-actin flows, leading to further accumulation of F-actin at the contact rim and the progressive redistribution of E-cadherin from the contact center to the rim. Eventually, this combination of actomyosin downregulation and flows at the contact determines the characteristic molecular organization, with E-cadherin and F-actin accumulating at the contact rim, where they are needed to mechanically link the contractile cortices of the adhering cells.

Annealed quantitative estimates for the quadratic 2D-discrete random matching problem - Clozeau, Nicolas; Mattesini, Francesco (Probability Theory and Related Fields)
We study a random matching problem on closed compact 2 -dimensional Riemannian manifolds (with respect to the squared Riemannian distance), with samples of random points whose common law is absolutely continuous with respect to the volume measure with strictly positive and bounded density. We show that given two sequences of numbers n and m=m(n) of points, asymptotically equivalent as n goes to infinity, the optimal transport plan between the two empirical measures μn and νm is quantitatively well-approximated by (Id,exp(∇hn))#μn where hn solves a linear elliptic PDE obtained by a regularized first-order linearization of the Monge-Ampère equation. This is obtained in the case of samples of correlated random points for which a stretched exponential decay of the α -mixing coefficient holds and for a class of discrete-time Markov chains having a unique absolutely continuous invariant measure with respect to the volume measure.

Laser-cavity locking utilizing beam ellipticity: accessing the 10−7 instability scale relative to cavity linewidth - Diorico, Fritz R; Zhutov, Artem; Hosten, Onur (Optica)
Frequency-stable lasers form the back bone of precision measurements in science and technology. Such lasers typically attain their stability through frequency locking to reference cavities. State-of-the-art locking performances to date had been achieved using frequency modulation based methods, complemented with active drift cancellation systems. We demonstrate an all passive, modulation-free laser-cavity locking technique (squash locking) that utilizes changes in spatial beam ellipticity for error signal generation, and a coherent polarization post-selection for noise resilience. By comparing two identically built proof-of-principle systems, we show a frequency locking instability of 5×10 −7 relative to the cavity linewidth at 10 s averaging. The results surpass the demonstrated performances of methods engineered over the last five decades, potentially enabling an advancement in the precision control of lasers, while creating avenues for bridging the performance gaps between industrial grade lasers with scientific ones due to the afforded simplicity and scalability.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Weighted packet selection for rechargeable links in cryptocurrency networks: Complexity and approximation - Schmid, Stefan; Svoboda, Jakub; Yeo, Michelle X (Theoretical Computer Science)
We consider a natural problem dealing with weighted packet selection across a rechargeable link, which e.g., finds applications in cryptocurrency networks. The capacity of a link (u, v) is determined by how many nodes u and v allocate for this link. Specifically, the input is a finite ordered sequence of packets that arrive in both directions along a link. Given (u, v) and a packet of weight x going from u to v, node u can either accept or reject the packet. If u accepts the packet, the capacity on link (u, v) decreases by x. Correspondingly, v's capacity on increases by x. If a node rejects the packet, this will entail a cost affinely linear in the weight of the packet. A link is “rechargeable” in the sense that the total capacity of the link has to remain constant, but the allocation of capacity at the ends of the link can depend arbitrarily on the nodes' decisions. The goal is to minimise the sum of the capacity injected into the link and the cost of rejecting packets. We show that the problem is NP-hard, but can be approximated efficiently with a ratio of (1+E) . (1+3) for some arbitrary E>0.
Keywords: General Computer Science; Theoretical Computer Science

RAF-like protein kinases mediate a deeply conserved, rapid auxin response - Kuhn, Andre; Roosjen, Mark; Mutte, Sumanth; Dubey, Shiv Mani; Carrillo Carrasco, Vanessa Polet; Boeren, Sjef; Monzer, Aline; Koehorst, Jasper; Kohchi, Takayuki; Nishihama, Ryuichi; Fendrych, Matyas; Sprakel, Joris; et al. (Cell)
The plant-signaling molecule auxin triggers fast and slow cellular responses across land plants and algae. The nuclear auxin pathway mediates gene expression and controls growth and development in land plants, but this pathway is absent from algal sister groups. Several components of rapid responses have been identified in Arabidopsis, but it is unknown if these are part of a conserved mechanism. We recently identified a fast, proteome-wide phosphorylation response to auxin. Here, we show that this response occurs across 5 land plant and algal species and converges on a core group of shared targets. We found conserved rapid physiological responses to auxin in the same species and identified rapidly accelerated fibrosarcoma (RAF)-like protein kinases as central mediators of auxin-triggered phosphorylation across species. Genetic analysis connects this kinase to both auxin-triggered protein phosphorylation and rapid cellular response, thus identifying an ancient mechanism for fast auxin responses in the green lineage.
Keywords: General Biochemistry; Genetics and Molecular Biology

Interface engineering modulation combined with electronic structure modification of Zn-doped NiO heterostructure for efficient water-splitting activity - Kiran, Gundegowda Kalligowdanadoddi; Singh, Saurabh; Mahato, Neelima; Sreekanth, Thupakula Venkata Madhukar; Dillip, Gowra Raghupathy; Yoo, Kisoo; Kim, Jonghoon (ACS Applied Energy Materials)
Production of hydrogen at large scale requires development of non-noble, inexpensive, and high-performing catalysts for constructing water-splitting devices. Herein, we report the synthesis of Zn-doped NiO heterostructure (ZnNiO) catalysts at room temperature via a coprecipitation method followed by drying (at 80 °C, 6 h) and calcination at an elevated temperature of 400 °C for 5 h under three distinct conditions, namely, air, N2, and vacuum. The vacuum-synthesized catalyst demonstrates a low overpotential of 88 mV at −10 mA cm–2 and a small Tafel slope of 73 mV dec–1 suggesting relatively higher charge transfer kinetics for hydrogen evolution reactions (HER) compared with the specimens synthesized under N2 or O2 atmosphere. It also demonstrates an oxygen evolution (OER) overpotential of 260 mV at 10 mA cm–2 with a low Tafel slope of 63 mV dec–1. In a full-cell water-splitting device, the vacuum-synthesized ZnNiO heterostructure demonstrates a cell voltage of 1.94 V at 50 mA cm–2 and shows remarkable stability over 24 h at a high current density of 100 mA cm–2. It is also demonstrated in this study that Zn-doping, surface, and interface engineering in transition-metal oxides play a crucial role in efficient electrocatalytic water splitting. Also, the results obtained from density functional theory (DFT + U = 0–8 eV), where U is the on-site Coulomb repulsion parameter also known as Hubbard U, based electronic structure calculations confirm that Zn doping constructively modifies the electronic structure, in both the valence band and the conduction band, and found to be suitable in tailoring the carrier’s effective masses of electrons and holes. The decrease in electron’s effective masses together with large differences between the effective masses of electrons and holes is noticed, which is found to be mainly responsible for achieving the best water-splitting performance from a 9% Zn-doped NiO sample prepared under vacuum.
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

A dynamic duo: Understanding the roles of FtsZ and FtsA for Escherichia coli cell division through in vitro approaches - Radler, Philipp; Loose, Martin (European Journal of Cell Biology)
Bacteria divide by binary fission. The protein machine responsible for this process is the divisome, a transient assembly of more than 30 proteins in and on the surface of the cytoplasmic membrane. Together, they constrict the cell envelope and remodel the peptidoglycan layer to eventually split the cell into two. For Escherichia coli, most molecular players involved in this process have probably been identified, but obtaining the quantitative information needed for a mechanistic understanding can often not be achieved from experiments in vivo alone. Since the discovery of the Z-ring more than 30 years ago, in vitro reconstitution experiments have been crucial to shed light on molecular processes normally hidden in the complex environment of the living cell. In this review, we summarize how rebuilding the divisome from purified components – or at least parts of it - have been instrumental to obtain the detailed mechanistic understanding of the bacterial cell division machinery that we have today.
Keywords: Cell Biology; General Medicine; Histology; Pathology and Forensic Medicine

A structurally precise mechanism links an epilepsy-associated KCNC2 potassium channel mutation to interneuron dysfunction - Clatot, Jerome; Currin, Christopher; Liang, Qiansheng; Pipatpolkai, Tanadet; Massey, Shavonne L.; Helbig, Ingo; Delemotte, Lucie; Vogels, Tim P; Covarrubias, Manuel; Goldberg, Ethan M. (Proceedings of the National Academy of Sciences of the United States of America)
De novo heterozygous variants in KCNC2 encoding the voltage-gated potassium (K+) channel subunit Kv3.2 are a recently described cause of developmental and epileptic encephalopathy (DEE). A de novo variant in KCNC2 c.374G > A (p.Cys125Tyr) was identified via exome sequencing in a patient with DEE. Relative to wild-type Kv3.2, Kv3.2-p.Cys125Tyr induces K+ currents exhibiting a large hyperpolarizing shift in the voltage dependence of activation, accelerated activation, and delayed deactivation consistent with a relative stabilization of the open conformation, along with increased current density. Leveraging the cryogenic electron microscopy (cryo-EM) structure of Kv3.1, molecular dynamic simulations suggest that a strong π-π stacking interaction between the variant Tyr125 and Tyr156 in the α-6 helix of the T1 domain promotes a relative stabilization of the open conformation of the channel, which underlies the observed gain of function. A multicompartment computational model of a Kv3-expressing parvalbumin-positive cerebral cortex fast-spiking γ-aminobutyric acidergic (GABAergic) interneuron (PV-IN) demonstrates how the Kv3.2-Cys125Tyr variant impairs neuronal excitability and dysregulates inhibition in cerebral cortex circuits to explain the resulting epilepsy.

Eva Benkova - Benková, Eva (Current Biology)
Eva Benkova received a PhD in Biophysics at the Institute of Biophysics of the Czech Academy of Sciences in 1998. After working as a postdoc at the Max Planck Institute in Cologne and the Center for Plant Molecular Biology (ZMBP) in Tübingen, she became a group leader at the Plant Systems Biology Department of the Vlaams Instituut voor Biotechnologie (VIB) in Gent. In 2012, she transitioned to an Assistant Professor position at the Institute of Science and Technology Austria (ISTA) where she was later promoted to Professor. Since 2021, she has served as the Dean of the ISTA Graduate School. As a plant developmental biologist, she focuses on unraveling the molecular mechanisms and principles that underlie hormonal interactions in plants. In her current work, she explores the intricate connections between hormones and regulatory pathways that mediate the perception of environmental stimuli, including abiotic stress and nitrate availability.

Nonadditivity in interactions between three membrane-wrapped colloidal spheres - Azadbakht, Ali; Meadowcroft, Billie; Majek, Juraj; Šarić, Anđela; Kraft, Daniela J. (Biophysical Journal)
Many cell functions require a concerted effort from multiple membrane proteins, for example, for signaling, cell division, and endocytosis. One contribution to their successful self-organization stems from the membrane deformations that these proteins induce. While the pairwise interaction potential of two membrane-deforming spheres has recently been measured, membrane-deformation-induced interactions have been predicted to be nonadditive, and hence their collective behavior cannot be deduced from this measurement. We here employ a colloidal model system consisting of adhesive spheres and giant unilamellar vesicles to test these predictions by measuring the interaction potential of the simplest case of three membrane-deforming, spherical particles. We quantify their interactions and arrangements and, for the first time, experimentally confirm and quantify the nonadditive nature of membrane-deformation-induced interactions. We furthermore conclude that there exist two favorable configurations on the membrane: (1) a linear and (2) a triangular arrangement of the three spheres. Using Monte Carlo simulations, we corroborate the experimentally observed energy minima and identify a lowering of the membrane deformation as the cause for the observed configurations. The high symmetry of the preferred arrangements for three particles suggests that arrangements of many membrane-deforming objects might follow simple rules.